Transformation of classical PSA and DSA into the form of conditional event tree: An approach of human action in time dependent core damage risk. (January 2022) - Najafi, Alireza; Shahsavand, Athena; Hosseini, Seyed Ali; Shirani, Amir Saeed; Yousefpour, Faramarz; Karimi, Kaveh
Highlights: A combination between DSA, PSA, and HRA for a steam line break accident. The DSA calculates the maximum available time for the operator depressurization. The SPAR-H method is used to calculate the HEP according to the operator timing. In PSA part, the CDFs are calculated based on the HEP. The PSV availability affect the CDFs that are highly dependent on the operator timing. Abstract: Although the accident progression in NPPs follows a dynamic trend, most industrial PSA studies used in the design process include static modeling with time-independent construction and without a well-defined linkage between the DSA and PSA. This is mostly due to the complicated methods for integration and post-processing procedures. This article aims to develop a straightforward combination process between DSA and PSA applicable in nuclear power plant safety analysis for considering the dynamic effects of operator task timing on the Core Damage Frequency (CDF). The case study is a Main Steam Line Break (MSLB) accident for a PWR. The combination approach includes a four-step procedure for the consideration of operator timing on the final core damage contribution. Thus, the CDFs are calculated based on different timings of human action, and the effects of timing on the CDF are presented in the form of a Conditional Event Tree (CET). According to the results, the total CDF is highly dependent on the HEP, and it can be reduced by providing additional time to the operator. The results also showed this additional time can be provided by the successful performance of the pressurizer safety valve as a passive device.